Sulfonated catalytic esterification of Madhuca indica oil using waste Delonix regia: L16 Taguchi optimization and kinetics. (February 2020) - Karmakar, Bisheswar; Ghosh, Bidipta; Samanta, Sucharita; Halder, Gopinath
Graphical abstract: Highlights: H2 SO4 impregnated carbonized flamboyant pods used as catalyst for esterification. L16 Taguchi optimization employed for Mahua oil methyl ester (MOME) synthesis. Reusability of developed catalyst assessed towards MOME yield up to 3 times. Esterification followed pseudo-first order kinetics with low EA and high A and k . Cost analysis of catalyst preparation showed feasibility of commercialization. Abstract: The reported study discusses fuel-grade mahua oil methyl esters production from Madhuca indica oil, utilizing Delonix regia pods as a precursor to develop activated carbon support for preparing sulfonated carbon catalyst by H2 SO4 impregnation. Raw pods were found to be thermally stable based on TGA analysis, making it suitable as raw material for catalyst synthesis. The catalyst is characterized using BET, XRD, SEM and FT-IR to check desired properties like surface area, porosity enhancement and doping of required functional groups. MOME production is optimized through L16 Taguchi design. Optimum yield of 97.04% is observed at 50 °C for 1 h with 4% w/w catalyst, methanol:oil of 6:1 and 1000 rpm. Catalyst load (1−4% w/w) affects the reaction most prominently, while methanol to oil molar ratio (3:1–12:1) is insignificant. The optimal product is characterized through ASTM standardized tests and gas chromatography analysis and conforms to acceptable biodiesel properties. The reaction adheres to pseudo-first order kinetics with low EA (4.257 kJ/mol) and high A (174.66 min −1 ). Catalyst shows appreciable reusability with >85% yield after 4 uses. Cost analysis of catalyst preparation shows that indigenously developed catalyst cuts down biodiesel production costs, thus the production process discussed is lucrative for commercialization.